Entre direitos e interesses: a atuação dos magistrados nos casos das hidrelétricas de Candonga e Aimorés-MG - Anabelle Santos Lages (2010)
In what measure the personal conditioning and the lows formation support the decisions from the judges. This work aims to comprehend how the personal and professional formation of the magistrates contributes to the construction of their reasons of decision. Having as a standard reference some empiric judicial decisions from the hydroelectric of Aimorés and Candonga, this research aims to study the argument (latent or manifest) proclaimed by some of magistrates who were involved in the elected cases. For this, initially, it aims to comprehend in what measure the formation science process of law, as well how the history of life of those magistrates involved in the analyzed cases, are giving support to their decisions. The problematic resides then in to assume the potentiality of the influence of the historic personal-fundaments in jurisprudence or, on the other aspect, to assume the presence of the forces no immediately juridical which are able to act in order to solve the elected cases. The analyze of the empiric reference beginning for a substratum which understands the dispute for the appropriation of the environment moved by an ideological dispute, has the purpose to identify in those decisions some elements able to reveal possible inclinations from the magistrates to appear as participants of those adopted references considering the hegemonic perspective of the paradigm of the Ecological Modernization, as also the views of the Environmental Justice. The election of Pierre Bourdieu as the theoretical reference finds its reason in his conception of judicial area, a space in which the laws neutrality and autonomy would be only rhetoric of a science that intends to be universal.